2016
DOI: 10.7747/jfes.2016.32.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Carbon Stock in Chronosequence Rehabilitated Tropical Forest Stands in Malaysia

Abstract: The loss and degradation in tropical forest region are some of the current global concern. Hence, these issues elevated the role of rehabilitated forests in providing ecological products and services. The information on the carbon stock is important in relation to global carbon and biomass use, but lacking from the tropical region. This paper reports the assessment of tree and soil carbon stock in a chronosequence rehabilitated tropical forest stands in Malaysia. The study site was at the UPM-Mitsubishi Forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…This order also held for average volume with values of 4.93 m 3 ha −1 , 3.30 m 3 ha −1 , 1.13 m 3 ha −1 , and 1.26 m 3 ha −1 . Our current study showed favourable growth performance of S. macrophylla in all study plots compared to the distribution of average tree height and DBH in rehabilitated forest stated by Jui et al [30] were mostly S. macrophylla aged 19 years with the value of 9.30 m and 8.16 cm, respectively. The growth pattern of planted S. macrophylla was examined in terms of MAIH, MAID, and MAIV ( Table 2).…”
Section: Resultssupporting
confidence: 64%
“…This order also held for average volume with values of 4.93 m 3 ha −1 , 3.30 m 3 ha −1 , 1.13 m 3 ha −1 , and 1.26 m 3 ha −1 . Our current study showed favourable growth performance of S. macrophylla in all study plots compared to the distribution of average tree height and DBH in rehabilitated forest stated by Jui et al [30] were mostly S. macrophylla aged 19 years with the value of 9.30 m and 8.16 cm, respectively. The growth pattern of planted S. macrophylla was examined in terms of MAIH, MAID, and MAIV ( Table 2).…”
Section: Resultssupporting
confidence: 64%
“…A study found that approximately 77 % N, 57 % phosphorus (P), and 44 % potassium (K) were translocated out of senescing leaves during mangrove leaf senescence (Wang et al, 2003). Foliar C is sequestrating continuously over the growing season (Kueh et al, 2013). The element re-translocation and C sequestration in leaves may lead to the foliar % C increase with time.…”
Section: Foliar Mercury Accumulation In Peatland Plantsmentioning
confidence: 99%